Muscle contracture diagnosis: the role of sonoelastography - Bruschetta, D.; Milardi, D.; Trimarchi, F.; Di Mauro, D.; Valenti, A.; Arrigo, A.; Valenti, B.; Santoro, G.; Cascio, F.; Vaccarino, G.; Cacciola, A. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Sonoelastography plays today a major role in musculoskeletal disease, showing minor muscle injuries not well appreciable in conventional B-mode ultrasonography and integrating it in major muscle injuries diagnosis. The aim of this study was to demonstrate the ability of elastosonography in the diagnosis of muscular contracture in football players presenting negative basic echography.